UJI AMILUM LIMBAH BATANG KELAPA SAWIT (Elaeis guineensis Jacq.) SEBAGAI BAHAN PENGIKAT PADA TABLET PARASETAMOL - Gusfarendi; Taurina, Wintari (Badan Penelitian dan Pengembangan Provinsi Kalimantan Barat, 2014)
Palm trunk the waste from rejuvenation of the palm plantation. This research was aim to test starch from palm trunk that used as binder in paracetamol tablet. This research used experimental method, which there was three formulas that used starch from palm trunk as a binder with variety concentrations of the F1(5%), F2(10%), F3(15%) and three comparative formulas that used amprotab as a binder with variety concentrations of the F4(5%), F5(10%), F6(15%). Wet granulation method was used to make the tablet. The tablet has evaluated and was statistical analiyzed One Way Anova. Evaluation of the tablets include weight uniformity test, hardness test, friability test, disintegration test, assay test and dissolution test. The result of evaluation tablets was all formula meet the requirements of tablet. Based on the result it can be used as a binder in paracetamol tablet. The optimum concentration as a binder was 10%.